2018
DOI: 10.1016/j.jsxm.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Ignorance Is Not Bliss: If We Don’t Understand Hypoactive Sexual Desire Disorder, How Can Flibanserin Treat It? Commentary

Abstract: Background Female sexual dysfunction (FSD) affects as many as 1 in every 3 women, with a significant portion of these with hypoactive sexual desire disorder (HSDD). These figures alone present significant psychological and pharmacologic challenges. Partly in response to this situation, in 2015 the US Food and Drug Administration approved flibanserin for the treatment of HSDD. This approval has drawn criticism on the grounds of efficacy and necessity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 48 publications
0
5
0
1
Order By: Relevance
“…In comparing L-arginine containing products to flibanserin, the only oral FDA-approved medication for the management of HSDD, adverse effects, population of study, and cost may be a consideration. Flibanserin carries a risk of hypotension, somnolence, syncope, fatigue, and carcinogenicity, and a REMS program has been enacted to ensure the safe use of flibanserin [41,42]. By contrast, limited adverse effects have been reported with L-arginine.…”
Section: Discussionmentioning
confidence: 99%
“…In comparing L-arginine containing products to flibanserin, the only oral FDA-approved medication for the management of HSDD, adverse effects, population of study, and cost may be a consideration. Flibanserin carries a risk of hypotension, somnolence, syncope, fatigue, and carcinogenicity, and a REMS program has been enacted to ensure the safe use of flibanserin [41,42]. By contrast, limited adverse effects have been reported with L-arginine.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, flibanserin has been clinically tested in premenopausal women in stable cis-gendered heterosexual relationships who reported either generalized or acquired HSDD [37]. In the clinical trials of flibanserin, women self-reported moderate improvements to the baseline assessment of HSDD [38,39].…”
Section: Therapeutic Effectivenessmentioning
confidence: 99%
“…Считается, что флибансерин способен модулировать эти нейромеди аторы в определенных зонах мозга и тем самым восста навливать необходимый баланс. К сожалению, большин ство комментариев по поводу эффективности флибансерина при СПВ у женщин в научных журналах не являются научными дискуссиями, экспертными клиническими мне ниями и не содержат анализа и интерпретации клиниче ских данных, а в большей степени содержат элементы сенсационности [40]. К недостаткам его стоит отнести высокую частоту побочных эффектов.…”
Section: репродуктивное здоровье и вртunclassified